Bach's cello suites transcription and interpretation for baritone saxophone - Twillert, Hendrik Van (2014)
Bach’s Suites for unaccompanied cello are a masterpiece of the Classical Western canon for their singularity and their creator’s mastery. A myriad of transcriptions were made throughout the centuries with bigger or lesser freedom. This thesis aims at revealing insights from the art of linear polyphony and its performance on a monophonic instrument such as the baritone saxophone. The study of the musical structure is supported by examples from the visual domain that help us to understand the notion of linear polyphony as a third-dimension object. The particularity of this study, in relation to the multiple existing literature about Bach’s music, is its focus on a wind player’s point of view, a saxophonist, which, given the restriction of the polyphonic possibilities of the instrument, reveals some discerning solutions on the performance, analysis and elaboration of the polyphonic thinking in Bach’s Suites. Similar to the relative novelty of the cello at Bach’s time, my work aims at giving as close as possible the same perspective of the music through a new vision and instrument. I analysed the art of linear polyphony and the techniques of elaboration of the melody in the Cello Suites, notably as a means to support the interpretation (e.g. articulation, phrasing, dynamics, vibrato, fingerings, etc.) and to devise a transcription of the Suites for the baritone saxophone. My choice felled on a transcription for baritone saxophone based on the manuscript from Anna Magdalena Bach, wishing to provide detailed guidelines for saxophonists who want to create a more informed interpretation. I hope to offer a better understanding of these works and to provide a reference to build and develop an individual interpretation, especially on the baritone saxophone.